(3bUjOI abgjIs - (3fhQ GdOjf CHh Ydj GdMSf Hf eSYhO GdjhSj,J (B1102 (3g` s ((3eMeO Hf CMeO Hf Ydis)
(3ChdgG (B:s
(3hHYO aGdebUhO PcQ eG WdH ef Gdcda hLhHkG Ch s
(3BNQgG (B:s
(3hJNW ef QH GdYdG HGdefi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B223s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs